A method for improving the resolution of single-frame off-axis holograms based on extrapolation iterations and Kronecker interpolation. (August 2022) - Zhao, Jieming; Gao, Zhan; Niu, Yuhao; Deng, Lin
Highlights: A new algorithm for increasing the resolution of single-frame off-axis digital holography is proposed. The algorithm is simple and effective in suppressing the zero-order spectrum. The algorithm increases the amount of spectral information at both low and high frequencies. Abstract: A method for improving the resolution of single-frame off-axis holograms based on extrapolation iteration and Kronecker interpolation is proposed to address the problem of low resolution of image sensors in digital holographic systems. Low-frequency information in the image is increased and the zero-order image is suppressed by the numerical computation in the frequency domain using the Kronecker interpolation method. High-frequency information outside the received plane is calculated using an extrapolation iterative algorithm. The obtained low-frequency and high-frequency information are then combined to improve the resolution of off-axis holography. Compared to conventional reconstruction methods, the proposed method eliminates the need to add complex optical elements to the optical path, greatly simplifying the optical system when increasing resolution. Simulation and optical experimental results demonstrate the feasibility of the proposed method.